Knowledge and approaches of married men applying to a primary healthcare center in Istanbul about IUD: A qualitative study - KARAVUŞ, MELDA; HIDIROĞLU, SEYHAN (KARE PUBL, 2019)
OBJECTIVE: This study aims to determine the knowledge and approach of men applying to a primary health care center about IUD by adopting qualitative research methods. METHODS: This study was qualitative research realized using an in-depth interview method. The interview was carried with 15 married men in a primary health care center in Umraniye, using 15 semi-structured interview questions. RESULTS: Knowledge of the men in this study about IUD and family planning was inadequate. Participants generally determined the advantages of IUD with its superiority over other methods. Adverse effects of IUD on women and men during intercourse were stated. Knowledge of men about IUD, its side effects and disadvantages were generally composed of misinformation and rumours about the subject. CONCLUSION: Men do not have adequate information and knowledge on family planning and IUD. Training provided by the health personnel might have a considerable role in demolishing misinformation and rumors and may augment the level of knowledge about IUD.
Keywords: Attitudes; intrauterine device; knowledge; married man; qualitative study; CONTRACEPTIVES; ATTITUDES; WOMEN